Calcaneal adduction in slow running: three case studies using intracortical pins. (4th May 2017) - Fischer, Katina Mira; Willwacher, Steffen; Arndt, Anton; Wolf, Peter; Brueggemann, Gert-Peter
Abstract : The aim of this study was to use bone-anchored markers to determine the bone movement of calcaneal adduction, eversion and tibial rotation in a global coordinate system and to describe the relationship of calcaneal adduction to tibial rotation. Furthermore, the amount of overall intra-foot motion in the transverse plane (metatarsal I relative to calcaneus) and its relationship to calcaneal adduction were quantified. Three male participants were assessed during slow running. A 10-camera motion analysis system was used for kinematic data capture of global bone orientations in 3D space for all bones of the foot and ankle complex. For the description of intrinsic articulations within the foot, the skeletal motion relative to the adjacent proximal segment in the transverse plane was calculated. Furthermore, the time of occurrence of maximum values was determined. The findings showed that calcaneal adduction of all participants amounted to 7.8 ± 4.8°, which exceeded the magnitude of calcaneal eversion (4.7 ± 3.1°). Although the inter-participant variability was high, considerable overall intra-foot motion in the transverse plane of the metatarsal I relative to the calcaneus was found to be 4.7 ± 4.6° and could be qualitatively related to calcaneal adduction. The present data provide evidence that next to calcaneal eversion, calcaneal adduction seems related to tibial rotation. Furthermore, overall intra-foot motion in the transverse plane seems related to calcaneal adduction. Controlling calcaneal adduction and overall intra-foot motion in the transverse plane may be a mechanism to control excessive tibial rotation in runners who suffer from overuse knee injuries. These findings could be used to provide an additional approach for future motion-control footwear design to control rearfoot adduction or overall within-foot motion.